2014
DOI: 10.1007/s00464-013-3369-6
|View full text |Cite
|
Sign up to set email alerts
|

Laminar and turbulent surgical plume characteristics generated from curved- and straight-blade laparoscopic ultrasonic dissectors

Abstract: Turbulent flow is disruptive to laparoscopic visibility with greater field obstruction and requires longer settling than laminar plume. Ultrasonic dissectors with straight blades have more consistent oscillations and generate more laminar flow compared with curved blades. Surgeons may avoid laparoscope smearing from maximum plume generation depending on blade geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…The SCUD performed similarly to the Harmonic ACE for vessel sealing times, burst pressures, collateral thermal damage, and seal failure rates in vivo in pigs . The SCUD had significantly decreased surgical smoke production compared to Harmonic ACE in ex vivo studies . Clinically, SCUD was successfully applied in a laparoscopic nephrectomy and a lymphadenectomy procedure in people .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SCUD performed similarly to the Harmonic ACE for vessel sealing times, burst pressures, collateral thermal damage, and seal failure rates in vivo in pigs . The SCUD had significantly decreased surgical smoke production compared to Harmonic ACE in ex vivo studies . Clinically, SCUD was successfully applied in a laparoscopic nephrectomy and a lymphadenectomy procedure in people .…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The SCUD had significantly decreased surgical smoke production compared to Harmonic ACE in ex vivo studies. 22,23 Clinically, SCUD was successfully applied in a laparoscopic nephrectomy and a lymphadenectomy procedure in people. 24 No data are available on the use of SCUD in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…Despite utilizing the same ultrasonic innovation, it has been reported that the cutting edge geometry of the device also affects the smoke production 11. USADs with straight sharp edges have more reliable oscillations and create more laminar flow than those with curved blades.…”
Section: Resultsmentioning
confidence: 99%
“…Laminar flow causes minimal visual obstruction by directing the aerosol downwards and dissipates immediately, while turbulent plume is directed erratically across the cavity. It causes maximum obstruction 0.3 s after activation and clears after 2 s. Ultrasonic dissectors with straight blades have more consistent oscillations and generate more laminar flow compared with curved blades [17] (Fig. 2).…”
Section: Cordless Uss Improvises Agility and Handlingmentioning
confidence: 99%
“…SonoSurg generated negligible plume obstruction (0.21 % of operating field), while Sonicision obstructed 4.8 % of operating field and ACE 26.63 % [16]. Kim et al [17] went on to identify two types of plume generations based on the blade geometry as well. Laminar flow causes minimal visual obstruction by directing the aerosol downwards and dissipates immediately, while turbulent plume is directed erratically across the cavity.…”
Section: Cordless Uss Improvises Agility and Handlingmentioning
confidence: 99%